Does tree size matter? : giraffe influence on African savanna ecosystem properties - Soutschka, Nadine (Department of Biological Sciences, 2017)
Trees alter the environment by affecting microclimate, soil properties and adding structural complexity to an otherwise single stratum system. It is known that the herbaceous understory of Savanna ecosystems is most productive at intermediate tree density, where the shade and nutrients from the tree are more influential than the competition with the tree. Tree density varies in savannas due to disturbances, such as fire and herbivory. Yet, disturbances do not only alter density but can affect entire tree structure. It has been found that chronic ungulate browsing influences whole tree size, as well as canopy size and shape. Giraffe in south of Kruger National Park browse heavily on Acacia nigrescens found on basalt-derived soils. I studied the influence of trees above the giraffe browse trap (>6 m) as opposed to trees in the browse trap (< 6 m) on savanna ecosystem properties. I compared grass biomass, soil moisture, soil organic matter, soil carbon and soil nitrogen beneath tall trees vs. short trees, as well as in the open vs. underneath trees. Ecosystem properties were estimated and compared between a giraffe impacted to a giraffe absent area. Giraffe impacted area overall yielded lower grass biomass, soil moisture, soil nitrogen and soil carbon. The consequence is a trophic cascade of events from increased giraffe decreasing fires and in tum increasing tree density and hence carbon sequestration. As giraffes replace a single large tree by several small trees, shows that their population size is key determinant of ecosystem properties.